2005
DOI: 10.1016/j.chembiol.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Antitumor Agent Chartreusin Involves the Oxidative Rearrangement of an Anthracyclic Polyketide

Abstract: Chartreusin is a potent antitumor agent with a mixed polyketide-carbohydrate structure produced by Streptomyces chartreusis. Three type II polyketide synthase (PKS) gene clusters were identified from an S. chartreusis HKI-249 genomic cosmid library, one of which encodes chartreusin (cha) biosynthesis, as confirmed by heterologous expression of the entire cha gene cluster in Streptomyces albus. Molecular analysis of the approximately 37 kb locus and structure elucidation of a linear pathway intermediate from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 55 publications
7
84
0
3
Order By: Relevance
“…The other sequences present in the KS and CLF trees are not located in well supported clades, leaving some doubt as to their placement, and therefore we will not discuss the incongruent clades between the various trees for these other sequences relative to each other. Two C-9 KRs were identified in the chartreusin gene cluster (35). One of these, ChaE, falls within the isochromanequinone clade.…”
Section: Resultsmentioning
confidence: 99%
“…The other sequences present in the KS and CLF trees are not located in well supported clades, leaving some doubt as to their placement, and therefore we will not discuss the incongruent clades between the various trees for these other sequences relative to each other. Two C-9 KRs were identified in the chartreusin gene cluster (35). One of these, ChaE, falls within the isochromanequinone clade.…”
Section: Resultsmentioning
confidence: 99%
“…In the sequenced Streptomyces avermitilis genome (24), there is an orthologue with sequence identity over 80% to each of these NsdA-like proteins and NsdA itself. Streptomyces chartreusis, producing a potent antitumor agent chartreusin, contains an NsdA homologue ChaR2 (27% identity), whose gene is inside the chartreusin gene cluster (49). Blast searching indicated that besides Streptomyces, several other actinomycetes (i.e., cellulolytic Thermobifida fusca, GenBank accession number NC_007333; symbiotic nitrogen-fixing Frankia sp.…”
Section: Vol 188 2006 Negative Gene Affecting Streptomyces Differenmentioning
confidence: 99%
“…The analyzed GNPs were selected based on the availability of MS n data in the METLIN database (26) (daunomycin, staurosporine, oleandomycin, vancomycin, tylosin, avermectin B1a, nystatin, aclacinomycin A, novobiocin, erythromycin A), the literature [spinosyn A (27), megalomicin (28), chartreusin (29), neocarzinostatin (30), lankamycin (31), Sch40832 (32), lomaiviticin C (33)], or generated for this study (phenalinolactone, amphotericin B, chalcomycin), and the availability of nucleotide sequences associated with biosynthetic gene clusters (Datasets S3 and S4). Eighteen of 20 analyzed GNPs could be connected successfully with their biosynthetic gene cluster by the MS-glycogenetic code ( Table 1).…”
Section: A Ms-glycogenetic Code Connecting Microbial Gnp Chemotypes Andmentioning
confidence: 99%